In vivo efficacy of oral and intralesional administration of 2-substituted quinolines in experimental treatment of new world cutaneous leishmaniasis caused by Leishmania amazonensis. - Fournet, A (1996)
The antileishmanial efficacies of 2-n-propylquinoline, chimanines B and D, 2-n-pentylquinoline, 2-phenylquinoline, 2-(3,4-methylenedioxyphenylethyl) quinoline, and two total alkaloidal extracts of Galipea longiflora were evaluated in BALB/c mice infected with Leishmania amazonensis or Leishmania venezuelensis. Animals were treated for 4 to 6 weeks postinfection with a quinoline by the oral route at 50 mg/kg of body weight twice daily for 15 days or by five intralesional injections at intervals of 4 days with a quinoline at 50 mg/kg of body weight. The reference drug, N-methylglucamine antimonate (Glucantime), was administered by subcutaneous or intralesional injection (regimens of 14, 28, or 56 mg of pentavalent antimony [Sbv] per kg of body weight daily). Twice-daily oral treatment with chimanine B at 50 mg/kg resulted in a decrease in lesion weight by 70% (P < 0.001) and a decrease in the parasite loads by 95% (P < 0.001). Five injections of chimanine B at intervals of 4 days reduced the lesion weight by 74% and the parasite loads in the lesion by 90% compared with the values for the group of untreated mice. Subcutaneous administration of N-methylglucamine antimonate at 28 mg of Sbv kg per day for 15 days reduced the parasite burden by 95% (P < 0.001), and five intralesional injections at the same concentration reduced the parasite burden by 96% (P < 0.001). Other 2-substituted quinolines, 2-n-propylquinoline administered by the oral and intralesional routes, 2-phenylquinoline administered by the oral route, 2-n-pentylquinoline administered by intralesional injection, and two total alkaloidal extracts of G. longiflora administered by the oral route, had intermediate effects. These findings suggest that chimanine B may be chosen as a lead molecule in the development of oral therapy against leishmaniasis.